Contemporary HRM Issues in the 21st century - Holland, Peter (Emerald Publishing Limited, 2019)
Contemporary HRM Issues in the 21st Century is an illuminating textbook for postgraduate students and active managers wanting to develop their understanding of issues and challenges emerging in the 21st century workplace from a HRM perspective. This edited collection, with contributions from experts in the field of HR policy development, is split into four sections. Section One explores the contemporary workforce and critical elements of managing HRM in a knowledge-based economy. Section Two focuses on psychological concerns for the individual at work, career management and emotional labour to better understand how to manage an increasingly diverse workforce. Section Three looks at managing HR issues in the workplace, such as crisis management, mental health and violence in the workplace. The final section of this book looks at current and emerging debates surrounding HRM, including: sustainable HRM; cyber-vetting; biological monitoring and surveillance; codes and conduct; job-design in the age of technology; and, Artificial Intelligence (AI). All of these are vital and often contentious areas within HRM policy-making and practice. This book sets out these debates and issues to engage both students and managers working in the fields of Global HRM and Human Resource policy-making.
Section I: The contemporary workplace. Chapter 1. HRM in the contemporary workplace / Peter Holland -- Chapter 2. Managing talent: a contemporary issue or a case of old wine in new bottles? / Peter Holland -- Section II: Managing the individual at work. Chapter 3. Psychological contracts / Ross Donohue and Tse Leng Tham -- Chapter 4. Career management in the 21st century / Ross Donohue and Tse Leng Tham -- Chapter 5. HRM and the service sector / Cathy Sheehan -- Section III: Managing the issues at work. Chapter 6. Risk and crisis management / Cathy Sheehan -- Chapter 7. Mental health and wellbeing at work / Hannah Meacham, Katharine Spaeth, Jillian Cavanagh and Timothy Bartram -- Chapter 8. The dark side of work / Ross Donohue and Peter Holland -- Section IV: Emerging issues at work -- Chapter 9. To test or not to test: drug and genetic testing in the 21st century workplace / Peter Holland and Tse Leng Tham -- Chapter 10. Turning the tables: employer and employee vetting: reputation management challenges in the information age / Debora Jeske and Peter Holland -- Chapter 11. Sustainable HRM: rhetoric versus reality / Renee Paulet -- Chapter 12. Work design in the 21st century: a case of back to the future or forward to the past? / Peter Holland, Kirsteen Grant and Tse Leng Tham -- Chapter 13. Codes of conduct: are they worth the paper they are written on? / Peter Holland and Xiaoyan Liang.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Personnel management; Business & Economics -- Human Resources & Personnel Management; Personnel & human resources management